Advances in nanomedicine and delivery systems for gastric cancer research - Wang, Sizhe; Li, Jilei; Zhang, Zhenyu; Cao, Shasha; Zhang, Zihan; Bian, Yifan; Xu, Yanchao; Ma, Chunzheng (Frontiers in Bioengineering and Biotechnology, 2025)
The early diagnosis rate of gastric cancer is low, and most patients are already at an advanced stage by the time they are diagnosed, posing significant challenges for treatment and exhibiting high recurrence rates, which notably diminish patients’ survival time and quality of life. Therefore, there is an urgent need to identify methods that can enhance treatment efficacy. Nanomedicine, distinguished by its small size, high targeting specificity, and strong biological compatibility, is particularly well-suited to address the toxic side effects associated with current diagnostic and therapeutic approaches for gastric cancer. Consequently, the application of nanomedicine and delivery systems in the diagnosis and treatment of gastric cancer has garnered increasing interest from researchers. This review provides an overview of recent advancements in the use of nanomaterials as drugs or drug delivery systems in gastric cancer research, encompassing their applications in diagnosis, chemotherapy, radiotherapy, surgery, and phototherapy, and explores the promising prospects of nanomedicine in the treatment of gastric cancer.